KONSEP PENDIDIKAN AQIDAH DALAM KITAB AQIDATUL AWAM KARYA SYEKH AHMAD MARZUKI DAN KORELASINYA DENGAN PENDIDIKAN AGAMA ISLAM - Sa'adah, Fatimah Nur; Ali Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Amid the complexity of social transformation driven by globalization, Aqidah education has become increasingly vital as a moral and spiritual bulwark for Muslim generation. One classical text that has endured for over a century and a half, remaining actively used in basic aqidah instruction is Aqidatul Awam by Shaykh Ahmad al-Marzuki, a Maliki-school scholar based in Makkah during the 19th century. Composed of 57 poetic verses (nadhom), this text presents the theology of Ahlussunnah wal Jama'ah in a systematic and easily memorized format, making it accessible to both laypeople and beginner students. This study aims to critically analyze the concept of aqidah education within the text and describe its correlation with Islamic Religious Education (PAI). Employing a library research approach with qualitative-descriptive analysis, primary data were drawn from the text of Aqidatul Awam and its commentaries, while secondary data came from relevant Islamic educational literature. The findings reveal: (1) Aqidatul Awam meets the standard of comprehensive (syumul) creed according to Hasan Al-Banna's framework through four dimensions, Ilahiyah establishing correct tawhid paradigm, Nubuwwah presenting the prophet as moral exemplar, Ruhaniyah cultivating muraqabah consciousness, and Sam'iyah providing eschatological life orientation while deepening love (mahabbah) for the Prophet; (2) its correlation with PAI manifests through aligned objectives in faith formation, concordance of rukun iman content, nadhom methodology as value internalization strategy, and shared orientation toward akhlakul karimah grounded in muraqabah awareness and afterlife consciousness. These findings affirm that classical Islamic intellectual heritage retains strong pedagogical relevance within contemporary Islamic educational contexts.